Automated coronary artery tree segmentation in coronary CTA using a multiobjective clustering and toroidal model-guided tracking method. (February 2021) - Du, Hongwei; Shao, Kai; Bao, Fangxun; Zhang, Yunfeng; Gao, Chengyong; Wu, Wei; Zhang, Caiming
Highlights: A new arterial tree segmentation framework is developed to extract entire coronary artery trees. A coronary artery tracking method based on toroidal model is constructed for solving most vessel bifurcation problems. A multi-objective clustering method is developed to distinguish the vascular structures in complicated background regions. Abstract: Background and objective: Accurate coronary artery tree segmentation can now be developed to assist radiologists in detecting coronary artery disease. In clinical medicine, the noise, low contrast, and uneven intensity of medical images along with complex shapes and vessel bifurcation structures make coronary artery segmentation challenging. In this work, we propose a multiobjective clustering and toroidal model-guided tracking method that can accurately extract coronary arteries from computed tomography angiography (CTA) imagery. Methods: Utilizing integrated noise reduction, candidate region detection, geometric feature extraction, and coronary artery tracking techniques, a new segmentation framework for 3D coronary artery trees is presented. The candidate regions are extracted using a multiobjective clustering method, and the coronary arteries are tracked by a toroidal model-guided tracking method. Results: The qualitative and quantitative results demonstrate the effectiveness of the presented framework, which achieves better performance than the compared segmentation methods in three widely used evaluation indices: the Dice similarity coefficient (DSC), Jaccard index and Recall across the CTA data. The proposed method can accurately identify the coronary artery tree with a mean DSC of 84 %, a Jaccard index of 74 %, and a Recall of 93 % . Conclusions: The proposed segmentation framework effectively segments the coronary tree from the CTA volume, which improves the accuracy of 3D vascular tree segmentation.